Monitoring ground arthropods in maize and pasture fields of São Miguel and São Jorge Islands: IPM-Popillia Project. - Teixeira, M. B. (2023)
ABSTRACT: The dataset presented here is the delivery of the European project “Integrated Pest Management of the Invasive Japanese Beetle, Popillia japonica (IPM-Popillia)”. This project aims to address the challenge of a new risk to plant health in Europe, the invasion of the Japanese beetle, Popillia japonica, and to provide an environmentally friendly IPM-Toolbox to control the pest in infested areas, protecting the agricultural systems and control this pest populations current in expansion across Europe. The present study targets to record, in maize and pasture fields of the Azores, ground arthropods with the potential to be used in futures Integrated Pest Management programs against P. japonica. A sampling program was conducted in two Islands (São Miguel and São Jorge) in the summer of 2022.